Examining the Relationship between Childhood Sleep Disorders and Neurodevelopmental Outcomes in Early Adolescence - Fizza Ashfaq, Muhmamad Qasim Khan, Khadija Tariq, Kainat Pervez, Muhammad Muslim Khan, Muhammad Sajjad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To examine the relationship between childhood sleep disorders and neurodevelopmental outcomes in early adolescence. Methods: A cross-sectional study was carried out at the Department of Pediatrics, Mardan Medical Complex, Mardan, from January 2022 to January 2023. A total of 72 participants aged 10–14 years were enrolled. Sleep patterns were assessed using a structured questionnaire adapted from the Children’s Sleep Habits Questionnaire (CSHQ). Cognitive and behavioral outcomes were evaluated with standardized tools, including subtests of the Wechsler Intelligence Scale for Children, Conners’ Rating Scale, and the Strengths and Difficulties Questionnaire. Demographic, lifestyle, and health-related data were also recorded. Statistical analysis was performed using chi-square and independent t-tests, with p < 0.05 considered significant. Results: Sleep disorders were identified in 47.2% of participants, with insomnia (30.6%) and sleep-disordered breathing (25.0%) being most common. Children with sleep disorders had significantly lower mean IQ scores (93.8 ± 10.2 vs. 101.5 ± 9.8, p = 0.01) and higher rates of attention deficits, academic underachievement, and emotional difficulties compared to peers without sleep problems. Daytime sleepiness and irregular sleep schedules were also significantly associated with poorer cognitive and behavioral outcomes. Lifestyle factors, including longer screen time and reduced physical activity, further contributed to poor sleep quality. Conclusion: Childhood sleep disorders are strongly associated with impaired neurocognitive and behavioral outcomes in early adolescence. Early identification and intervention strategies, including parental guidance on healthy sleep routines and clinical management of sleep-related breathing disorders, are essential to improve developmental trajectories. Keywords: Childhood sleep disorders, Neurodevelopment, Insomnia, Sleep-disordered breathing, Adolescence, Cognitive function